2020
DOI: 10.1038/s41415-020-1919-6
|View full text |Cite
|
Sign up to set email alerts
|

Teledentistry from a patient perspective during the coronavirus pandemic

Abstract: Objective Evaluation of patient experience when utilising teledentistry during the coronavirus (COVID-19) pandemic. Methods We designed a ten-item, five-point Likert-scale questionnaire assessing: 1) patient satisfaction; 2) ease of use; 3) the effectiveness including increasing access to clinical services; 4) reliability of the teledentistry system; and 5) usefulness for patients. Fifty-two patients completed the survey and data was analysed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
111
2
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 12 publications
6
111
2
19
Order By: Relevance
“…We report outcomes from the largest evaluation to date of teledentistry within Oral Surgery incorporating patient experience and clinical effectiveness, which demonstrated a very positive perception of telephone consultations. This is in-line with findings from a recent study of 52 patients which found patients that used virtual clinics and telephone consultations had 97% and 94% satisfaction respectively [ 15 ]. Only telephone clinics were assessed in our study as these are more widely available across this particular Trust at the time of the study.…”
Section: Discussionsupporting
confidence: 90%
“…We report outcomes from the largest evaluation to date of teledentistry within Oral Surgery incorporating patient experience and clinical effectiveness, which demonstrated a very positive perception of telephone consultations. This is in-line with findings from a recent study of 52 patients which found patients that used virtual clinics and telephone consultations had 97% and 94% satisfaction respectively [ 15 ]. Only telephone clinics were assessed in our study as these are more widely available across this particular Trust at the time of the study.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, teledentistry has become part of the practice landscape and has important implications for care delivery, organization, quality assessment, and financing. 3 Dental schools have adopted remote learning and there are unanswered questions on how seismic curricular changes have affected student wellness and clinical skill acquisition. COVID-19 has revitalized conversations on how to modernize pedagogy in dentistry, which includes technology-driven clinical simulation and virtual reality.…”
Section: Issues That Mattermentioning
confidence: 99%
“…Around the world, practitioners and policymakers look to scientists for guidance on standards of care that ensure safety. For instance, teledentistry has become part of the practice landscape and has important implications for care delivery, organization, quality assessment, and financing 3 . Dental schools have adopted remote learning and there are unanswered questions on how seismic curricular changes have affected student wellness and clinical skill acquisition.…”
Section: Issues That Mattermentioning
confidence: 99%
“…Since the pandemic onset, dental teams have recuperated, evolved, and redefined their role, attempting to meet patients’ demands. We have had to embrace a whole set of new ‘technical’ abilities to become more adaptable users of modern technologies, getting to know telehealth and online consultation methods [ 4 , 5 , 6 ] which have become an integrated part of daily life. They seemingly enhanced our communication skills while providing a remote triaging or dealing with phobic and medically compromised individuals without pharmacological anxiety management measures [ 3 ].…”
mentioning
confidence: 99%